Healthcare worker perceptions of the FAST TB infection control strategy - D.B. Tierney; R.R. Nathavitharana; L. Cummins; K. Tintaya; A. Biewer; R. Guerrero; L. Lecca; L.R. Hirschhorn; E.A. Nardell; A.K. Nelson (Public Health Action)
BACKGROUND: The FAST (Find cases Actively, Separate safely and Treat effectively) TB infection control (TB-IC) strategy decreases the time-to-TB diagnosis and treatment. We examined healthcare workers’ (HCW) perceptions of FAST implementation at a tertiary referral hospital in Lima, Peru. METHODS: From August 2016 to December 2019, we conducted 24 interviews and four focus groups (n = 14) with a diverse population of HCWs and other stakeholders involved throughout the TB care cascade. We used inductive analysis to identify emergent themes, used Dedoose to code transcripts accordingly, and developed a narrative using reflexive thematic analysis. RESULTS: We identified three emergent themes: 1) FAST impact on TB care, 2) FAST impact on TB-IC and 3) FAST impact on hospital culture. FAST was felt to improve the speed of TB screening, diagnosis and treatment. TB specialists recognized that by expediting diagnosis and treatment, FAST likely decreased transmission. Healthcare workers appreciated that FAST improved care coordination along the TB care cascade. FAST changed hospital culture related to the prioritization of TB-IC. CONCLUSION: HCWs perceived that FAST, implemented by a dedicated external team, was an acceptable and effective TB-IC strategy that improved care coordination and overall TB quality of care.